Real-Time Voltammetric Assay of Lead Ion in Biological Cell Systems - Ly, Suw Young (Toxicol Res, 2009)
Trace lead detection for cyclic voltammetry (CV) and square-wave (SW) stripping voltammetry was performed using mercury immobilized onto a carbon nanotube electrode (HNPE). Using the characteristics of mercury and the catalytic carbon nanotube structure, a modified technique, the 0.45 µg/l detection limit of lead ion was attained. The developed method can be applied to pond water, fish tissue, plant tissue, and in vivo direct assay.